12 tips for effective questioning in medical education. (1st December 2020) - Pylman, Stacey; Ward, Amy
Abstract: Questioning is one of the most frequently used and powerful teaching strategies across levels and settings in medical education. Although the concept of asking questions may seem like a simple practice, many medical educators lack pedagogical training. When effectively executed, questioning can elicit positive outcomes in learner participation, concentration, and understanding of content. When used incorrectly, questioning can leave learners feeling singled out and not in a position to learn, or worse – threatened or humiliated. There is a lot of literature in medical education about what ineffective questioning looks like, but little about how to enact effective questioning, such as what kind of questions should be asked and how to design those questions to improve learning. The following twelve tips will help medical educators be purposeful and effective as they plan, ask, and analyze questions in classroom or clinical settings.